2014
DOI: 10.1007/s10827-014-0495-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of frequency mismatch in neuronal communication through coherence

Abstract: Neuronal gamma oscillations have been described in local field potentials of different brain regions of multiple species. Gamma oscillations are thought to reflect rhythmic synaptic activity organized by inhibitory interneurons. While several aspects of gamma rhythmogenesis are relatively well understood, we have much less solid evidence about how gamma oscillations contribute to information processing in neuronal circuits. One popular hypothesis states that a flexible routing of information between distant po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 40 publications
4
45
0
Order By: Relevance
“…The observed role of detuning is in agreement with a previous study in the rat hippocampus (Akam et al, 2012), in which optogenetic entrainment strength and phase of gamma rhythms were dependent on the frequency-detuning. The results also agree with theoretical conceptions on oscillatory interactions (Ermentrout and Kopell, 1984; Hoppensteadt and Izhikevich, 1998; Sancristóbal et al, 2014; Tiesinga and Sejnowski, 2010). We suggest that small detuning values (mainly <Δ10Hz) reported in the present study and much larger shifts in the gamma frequency-range (25-50Hz to 65-120Hz) reported in the rat hippocampus and cortex (Colgin et al, 2009) represent different but complementary mechanisms for controlling gamma synchronization.…”
Section: Discussionsupporting
confidence: 89%
“…The observed role of detuning is in agreement with a previous study in the rat hippocampus (Akam et al, 2012), in which optogenetic entrainment strength and phase of gamma rhythms were dependent on the frequency-detuning. The results also agree with theoretical conceptions on oscillatory interactions (Ermentrout and Kopell, 1984; Hoppensteadt and Izhikevich, 1998; Sancristóbal et al, 2014; Tiesinga and Sejnowski, 2010). We suggest that small detuning values (mainly <Δ10Hz) reported in the present study and much larger shifts in the gamma frequency-range (25-50Hz to 65-120Hz) reported in the rat hippocampus and cortex (Colgin et al, 2009) represent different but complementary mechanisms for controlling gamma synchronization.…”
Section: Discussionsupporting
confidence: 89%
“…While in many cases coupling merely coordinates dynamical regimes that are already present in the isolated elements, in others it underlies the emergence of novel behaviors that would not exist in the absence of interaction between the elements [4,5]. In the brain, examples of such emergent behavior exist at the microscopic scale of networks of neurons, in the form of, for instance, collective oscillations arising from a balance between excitation and inhibition [6,7] and recurrent up/down dynamics [8]. Much less is known, however, about the emergent behavior of the brain at the mesoscopic level of coupled brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 44 communication through coherence (CTC ) not only provides the means to communicate 45 from one network to another, but it also provides the means to control the 46 communication, because only networks with an appropriate phase synchrony with the 47 sender network can tune in to the spiking activity they receive. However, there are two 48 clear limitations to this mechanism: (1) Experimentally observed oscillations are not 49 stable over long enough times to support their role in communicating spiking 50 activity [22], and (2) The mechanisms by which two networks can generate coherent 51 oscillations have so far remained quite obscure (however, see [23,24]).…”
mentioning
confidence: 99%
“…(pulse packets) which can be quantified by the number of spikes in the volley 23 (α = 50 − 100 spikes) and their temporal dispersion (σ ≈ 1 − 10 ms), measuring the 24 degree of synchronization of the spiking activity in the volley [18,20]. Several studies 25 have demonstrated that the downstream effect of a pulse packet depends both on α and 26 σ (see [7] for a review).…”
mentioning
confidence: 99%